A Semiotic Analysis of Cultural and Religious Symbolism in the Ornaments of An-Nur Grand Mosque Riau - Fauziah, Fauziah (Medan Resource Center, 2025)
This study explores the cultural and semiotic meanings embedded in the ornamental designs of the An-Nur Grand Mosque in Riau, Indonesia. Ornamentation in Islamic architecture serves not only as aesthetic enhancement but also as a medium for conveying symbolic and cultural values. Grounded in Marcel Danesi's semiotic theory, this research aims to analyze and interpret the types, forms, and meanings of ornaments present in the mosque's architectural elements. Employing a descriptive qualitative method, the data were collected through field observations, photographic documentation, and literature review. The study focuses on identifying both the visual characteristics and symbolic interpretations of the mosque’s ornaments. The findings reveal that the An-Nur Grand Mosque features two dominant types of ornaments: Arabic and Malay. These types are further expressed through two primary forms, geometric and floral designs. Arabic ornaments often reflect spiritual values and religious symbolism, while Malay ornaments incorporate local cultural identity and aesthetic sensibilities. Geometric patterns convey concepts of infinity and divine unity, while floral motifs symbolize growth, beauty, and the connection between nature and spirituality. This research contributes to the broader field of cultural and semiotic studies by demonstrating how architectural ornamentation in sacred spaces serves as a rich semiotic system that bridges religious ideology and local cultural expressions. The study underscores the importance of reading architectural elements as meaningful texts that reflect both universal and localized identities in Islamic art and architecture.